Karl Polanyi - Isaac, Barry L. (Edward Elgar Publishing, 2005)
This unique Handbook contains substantial and invaluable summary discussions of work on economic processes and issues, and on the relationship between economic and non-economic areas of life. Furthermore it describes conceptual orientations that are important among economic anthropologists, and presents summaries of key issues in the anthropological study of economic life in different regions of the world. Its scope and accessibility make it useful both to those who are interested in a particular topic and to those who want to see the breadth and fruitfulness of an anthropological study of economics.
Keywords: economic anthropology; economics and finance; social policy and sociology

What We Need to Know About the Social Economy A Guide for Policy Research - PRI Project (Government of Canada, 2005)
This guide provides background on the social economy, identifies research issues whose examination would support the development of policies and programs, provides suggestions for how this research might be conducted, and points to some useful information sources. KM: Gov't commissioned - New Approaches for Addressing Poverty and Exclusion
Keywords: Canada; borderline; government of canada; grey literature; social economy